PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM: (Studi Pada Sub Sektor Industri Pariwisata Periode 2015 - 2019) - Subur Karyatun (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study is to examine the effect of fundamental factors on stock returns. The fundamental factors in this study consist of: (1) CR (Current Ratio), (2) TATO (Total Assets Turn Over), (3) ROE (Return on Equity), and (4) FATO (Fixed Assets Turn Over), whereas. The population of this study are all companies listed on the Indonesia Stock Exchange (IDX) in the tourism industry sub-sector. The period in the study was carried out from 2015 to 2019. From this population, the sample selection used purposive sampling: (1) Companies that published financial statements 5 times for the period from December 2015 to December 2019, (2) Companies that carried out stock price transactions the period from 2015 to 2019. With these criteria, a sample of 19 companies was obtained. Conducted during the research period of 5 (five) years and the method of analysis used linear regression analysis with the WarpPLS test tool. The results of this study by direct testing of CR and FATO on Stock Return showed negative and significant. TATO, ROE on Stock Return shows a positive and significant effect.